2022
DOI: 10.3389/fmicb.2022.749396
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profile of the Fungus Cryomyces antarcticus Under Simulated Martian and Space Conditions as Support for Life-Detection Missions on Mars

Abstract: The identification of traces of life beyond Earth (e.g., Mars, icy moons) is a challenging task because terrestrial chemical-based molecules may be destroyed by the harsh conditions experienced on extraterrestrial planetary surfaces. For this reason, studying the effects on biomolecules of extremophilic microorganisms through astrobiological ground-based space simulation experiments is significant to support the interpretation of the data that will be gained and collected during the ongoing and future space ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 119 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…One other important term for all three clusters is “biosignature” ( Figure S2 ). Missions seeking bio-signatures in situ on Mars and icy moons of our Solar System are a challenging task because organisms and their metabolic products may be destroyed by the harsh conditions experienced on irradiated planetary and icy-moon surfaces [ 114 , 115 , 116 , 117 , 118 ]. Bio-signature search in distant exo-planets is a rather different task and focuses on the spectral analysis of atmospheres.…”
Section: Discussionmentioning
confidence: 99%
“…One other important term for all three clusters is “biosignature” ( Figure S2 ). Missions seeking bio-signatures in situ on Mars and icy moons of our Solar System are a challenging task because organisms and their metabolic products may be destroyed by the harsh conditions experienced on irradiated planetary and icy-moon surfaces [ 114 , 115 , 116 , 117 , 118 ]. Bio-signature search in distant exo-planets is a rather different task and focuses on the spectral analysis of atmospheres.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that osmolytes production increases after simulated space stressors, including dehydration and vacuum ( Gevi et al, 2022 ). Also, other studies demonstrated a predominant production of glycerol as the most abundant osmolytes in Aspergillus wentii after growing on salt media ( Danilova et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This research paves the way for in situ screening for exoplanetary biosignatures, where microbes could be grown under natural conditions similar to those occurring on other planets, after which their metabolic traits can be tracked as potential biosignatures. Gevi et al (2022) used a similar approach to mimic Martian conditions in vitro and grow the black fungus Cryomyces antarcticus. Metabolomic profiles of the cultures increased the range of possible biosignatures of life on Mars.…”
Section: In Situ Diffusion-based Devices In Extreme Environmentsmentioning
confidence: 99%